TINJAUAN YURIDIS STATUS DOWN PAYMENT (UANG MUKA) DALAM JUAL BELI TANAH DIKAITKAN DENGAN UNDANG-UNDANG NO. 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Andika, Dandi Dwi; Herlina, Elis (Universitas Ekasakti, 2023)
In practice, land sale and purchase agreements are sometimes faced with various problems, including defaults on the part of the buyer or seller where the parties are negligent or deliberately do not fulfill their achievements, thus causing the end of the sale and purchase agreement. For the purpose of this research, namely to find out and examine the down payment status due to the cancellation of land sale and purchase transactions linked to Law Number 8 of 1999 concern on Consumer Protection and to find the alternative dispute resolution that can be taken related to down payments related to land sale and purchase transactions . This study applies normative juridical research methods and is carried out descriptively. From the results of the research, the status of down payments in buying and selling land is associated with Law no. 8 of 1999, namely that one party cannot cancel a purchase because there is already a down payment. However, in some agreements it is possible to agree on the return of the down payment. If the cancellation is caused by the seller's default, thus he is obliged to return the down payment to the buyer, but if it is caused by the buyer's default, then the seller is not obliged to return the down payment. Dispute resolution that can be carried out by the buyer can be carried out amicably. If it doesn't work, then you can take the non-litigation route. To minimize this incident, the buyer should be more careful when carrying out the sale and purchase of land also need to make a binding sale and purchase deed in front of a notary as a perfect and valid witness and evidence.